Dampak Kebijakan Moneter Terhadap Pertumbuhan Usaha Kecil Dan Menengah (Ukm) Di Indonesia - Shelviodifahni; Pohan, Syarifah Putri Aminah; Lubis, Siti Tatia (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This study aims to gain an in-depth understanding of how monetary policy affects the development of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The research employs a qualitative approach through literature review, documentation, and semi-structured interviews with MSME actors and financial practitioners. The main focus is on the perceptions of business actors regarding the impact of changes in interest rates and liquidity on access to financing, revenue growth, and business sustainability. The findings indicate that monetary policy, particularly in the form of interest rate reductions and liquidity easing, is perceived positively by MSME actors, although its implementation still faces structural challenges. This study concludes that the effectiveness of monetary policy in promoting MSMEs is highly influenced by the role of financial intermediaries and the broader macroeconomic conditions.